Narrative Analysis of the Web Series "Suka Duka Berduka" to Review the Relationship between Characters - Syahyuni Srimayasandy (MEDIASI : Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2023)
This article discusses the relationship between characters in the Indonesian web series ‘Suka Duka Berduka’. This web series is an Indonesian web series with conflicts over inheritance within the family. This study uses the Aktan model approach made by Greimas. Through this approach, it can be concluded that in the web series ‘Suka Duka Berduka’ characters cannot only occupy a position. However, it can move around according to the needs of the story. For example, a sending character can become a receiving character. Thus, it can be concluded that in a story the position of the actor is not always constant, but can be flexible according to the needs of the story. This study also supports the previous argument, where the position of Aktan does not have to be filled with a character or figure but can also be a condition or situation.